항공 MRO산업 분석을 통한 해군 MRO 발전에 대한 연구 - 신승민(Seungmin Shin); 오경원(Kyungwon Oh) (항공우주시스템공학회지, 2020)
In this paper, a plan to expand the scale of the domestic MRO industry was proposed by finding the technical common points between the aviation MRO and naval vessel MRO industries. The aviation MRO industry is led by Europe, North America, and Singapore. Europe and North America have very large aviation industries. The reason for the development of the MRO industry in Singapore is that the aviation MRO and ship MRO industries gathered to expand the industrial scale. The MRO field is an industry that spans all fields from research & development, production, manufacturing, operation, disposal, and crew training. The MRO industry is divided into military and civilian use. However, most of them are only differences in the needs of users, and there are no significant technical differences. The weapon system used by the military is steadily developing. It is impossible for the military to maintain all equipment at a time when troops are reduced. For that reason, it is necessary to share roles in each field. There is a need for an MRO industry in which civil and military operations cooperate to maintain all weapon systems at optimal performance. And the MRO industry development should be based on the civil market. The scale of the MRO industry should be expanded by gathering equipment commonly used in aircraft and naval vessels. This can increase military availability and reduce maintenance budgets. 본 논문에서는 항공 MRO와 해군함정 MRO 산업의 기술공통점을 찾아 국내 MRO 산업규모를 확대할 수 있는 방안을 제시했다. 항공 MRO산업는 유럽과 북미, 싱가폴에서 주도하고 있다. 유럽과 북미는 항공산업 규모가 매우 크다. 그리고 싱가폴에서 MRO산업이 발전한 이유는 항공 MRO와 선박 MRO 산업이 모여 산업규모를 확대했기 때문이다. MRO분야는 연구개발, 생산, 제조, 운용, 폐기 및 승조원 교육훈련까지 전 분야에 걸친 산업이다. MRO산업은 군수용과 민수용으로 구분된다. 하지만 대부분 사용자의 요구사양 차이일 뿐 기술적 차이는 크게 없다. 군이 사용하는 무기체계는 꾸준하게 발전하고 있다. 병력이 감축되는 시기에 군이 모든 장비를 유지보수 하는 것은 불가능하다. 그 때문에 각 분야별로 역할 분담 필요하다. 모든 무기체계를 최적 성능으로 유지하기 위해 민과 군이 협력하는 MRO 산업 필요하다. 그리고 MRO 산업육성은 민수를 기반으로 이뤄져야 한다. 항공기와 해군함정에서 공통적으로 사용되는 장비를 모아 MRO 산업규모를 확대해야 한다. 이를 통해 군의 가용성 확대와 정비예산을 절감할 수 있다.